Edukasi Pola Makan Sehat: Kurangi Konsumsi Makanan Cepat Saji Untuk Hidup Lebih Sehat - Effendy, Devi Savitri; Muchtar, Febriana; Bahar, Hartati; Tossepu, Ramadhan; Namrin, Najwa; Aremanita, Nazhifa Nahda; Ainun, Nur Hikmah; Apriyani, Desi; Effendy, Lisnawati; Zamzam, Zamzam; Kalisi, Hadi (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The program "Edukasi Pola Makan Sehat Bagi Mahasiswa: Kurangi Konsumsi Makanan Cepat Saji Untuk Hidup Lebih Sehat" aimed to enhance students' awareness of the importance of a healthy diet. The initiative focused on reducing the consumption of high-sodium, spicy, and sugary foods, such as ayam geprek and iced tea, which are commonly consumed by students due to their convenience and affordability. Conducted through interactive face-to-face sessions, the program utilized lectures, discussions, and practical recommendations for healthier menu alternatives. Despite limitations such as restricted participant reach, higher operational costs, and inflexible scheduling for students with tight academic timetables, the program effectively promoted healthier lifestyle choices. The outcomes demonstrated a positive influence on students' dietary habits, offering a foundation for sustainable behavior change toward healthier eating practices.